Association of atrial fibrillation with infectivity and severe complications of COVID‐19: A nationwide cohort study. Issue 6 (17th February 2022) - Park, Jin; Shin, Jae Il; Kim, Dong‐Hyeok; Park, Junbeom; Jeon, Jimin; Kim, Jinkwon; Song, Tae‐Jin
Abstract: Infection is associated with the occurrence, recurrence, and progression of atrial fibrillation (AF), and is also closely related to poor prognosis. However, studies of the relationship between infectivity and severe complications of coronavirus infectious disease‐19 (COVID‐19) with a history of AF are limited. To estimate infectivity and severity of complications in COVID‐19 patients with a history of AF, this study was done. From the Korean nationwide COVID‐19 dataset, 212 678 participants with at least one severe acute respiratory syndrome coronavirus 2 (COVID‐19) test were included between January 1 and June 4, 2020. AF was defined according to at least two outpatient hospital visits or one admission with an ICD‐10 code of "I48" before the COVID‐19 test. To investigate the association of AF with infectivity and severe complications of COVID‐19, 1:4 ratio propensity score matching (PSM) was performed. Severe complications of COVID‐19 were defined as a composite outcome of mechanical ventilation, intensive care unit admission, and death within 2 months after COVID‐19 diagnosis. Among 212 678 participants who underwent the COVID‐19 test, there were 7713 COVID‐19 positive patients. After PSM, COVID‐19 PCR positivity did not show a significant difference according to the presence of AF (odds ratio [OR]: 0.79, 95% confidence interval [CI]: [0.60–1.04]). Of 7713 COVID‐19 patients, 62 (0.8%) had a history of AF and severe complications occurred in 444 (5.7%) patients. After PSM, AF was associated with the development of severe complications (OR: 2.04, 95% CI: [1.10–3.79]) and mortality (OR: 2.09, 95% CI: [1.01–4.31]) of COVID‐19. We found that AF was associated with an increased risk of severe complications in COVID‐19 infected patients. RESEARCH HIGHLIGHTS: It has been known that the presence of comorbidities is associated with worse outcomes in COVID‐19 infection. Based on the Korean nationwide COVID‐19 dataset, 212 678 participants underwent the COVID‐19 real‐time reverse transcription‐polymerase chain reaction test (January 1–June 4, 2020), we evaluated the infectivity and severe complications of COVID‐19 according to the presence of atrial fibrillation. COVID‐19 positivity rate did not differ according to the presence of atrial fibrillation. Among patients infected with COVID‐19, the presence of atrial fibrillation was significantly associated with increased risk for severe complications and mortality within 2 months after COVID‐19 diagnosis.